The impact of sphingomyelin on the pathophysiology and treatment response to olipudase alfa in acid sphingomyelinase deficiency - Monica Kumar; Mario Aguiar; Andreas Jessel; Beth L. Thurberg; Lisa Underhill; Holly Wong; Kelly George; Vanessa Davidson; Edward H. Schuchman (Genetics in Medicine Open, 2024)
Acid sphingomyelinase deficiency (ASMD) is a rare progressive genetic disorder caused by pathogenic variants in the SMPD1 gene causing low or absent activity of the enzyme acid sphingomyelinase, resulting in subsequent accumulation of its substrate, sphingomyelin. Signs and symptoms of excessive lysosomal sphingomyelin storage, such as hepatosplenomegaly and pulmonary impairment, and in a subset of patients, progressive neurological manifestations, have long been recognized as hallmarks of the disease. Uncontrolled accumulation of sphingomyelin has important and complex downstream metabolic and immunologic consequences that contribute to the disease burden. This review article expounds on the complex and multifaceted role of sphingomyelin in the pathophysiology of ASMD and discusses the animal studies and human interventional trials demonstrating that sphingomyelin and its related metabolites are linked to ASMD clinical manifestations, disease burden, and response to treatment. The relationship between the diverse manifestations of ASMD and sphingomyelin accumulation and the connections between sphingomyelin clearance and reversal of the noncentral nervous system manifestations by olipudase alfa therapy also are described.